Pengaruh Disiplin Kerja Dan Evaluasi Kerja Terhadap Kinerja Karyawan Pada Hotel Aston Batam Hotel & Residence - Fakhrul Rizal,; Sri Sundari,; Marisi Pakpahan, (Manajemen Kreatif Jurnal, 2024)
This research aims to examine the combined influence of (1) work discipline and job satisfaction on employee performance; (2) work discipline on employee performance; and (3) job satisfaction on employee performance. The research design employed is quantitative causal. The subjects of this study encompass all employees at Aston Batam Hotel & Residence, with a population of 100. Data collection was conducted through a survey using a questionnaire as the research instrument. The collected data were analyzed using multiple linear regression while adhering to classical assumptions. The results of the analysis indicate that both work discipline and job satisfaction, when considered together, significantly affect employee performance. Furthermore, work discipline and job satisfaction individually and significantly contribute to employee performance.